Fully bio-based and biodegradable polylactic acid/poly(3-hydroxybutirate) blends: Use of a common plasticizer as performance improvement strategy - D'amico, David Alberto (2016)
Biodegradable polymeric blends based on poly(3-hydroxybutyrate) (PHB) and polylactic acid (PLA) were prepared by melt mixing. Trybutyrin, a bio-based plasticizer, was added at a fixed proportion in all blends. Crystal structure, percent crystallinity, miscibility, mechanical properties and permeation of fully biodegradable PHB/PLA blends were investigated in detail by Differential Scanning Calorimetry (DSC), Fourier Transformed Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), tensile tests and water vapor permeation tests. From the thermal test, two glass transition temperatures were found for the whole range of compositions, which reveals the immiscibility between PHB and PLA. Moreover, the biphasic melt further confirms this fact. Tensile tests showed an increase in the elongation at break with the PLA content. SEM images reveal debonding between the interfacial surfaces, which justifies the increase in the elongation at break. Water vapor permeation values for blends were slightly higher than that of the plasticized pristine polymer. The plasticized polymer blends showed valuable properties to extend the applications of PHB and PLA.